2011
DOI: 10.1038/modpathol.2011.100
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p63 is the sole independent marker of aggressiveness in localised (stage I–II) Merkel cell carcinomas

Abstract: Merkel cell carcinoma of the skin is a malignant neuroendocrine tumour, whose prognostic criteria are a matter of dispute. Specifically, no predictor is presently available in stage I-II tumours. We collected clinical and follow-up data from 70 Merkel cell carcinomas of the skin. The same cases were studied for p63 expression by immunohistochemistry, by reverse-transcription PCR (RT-PCR) and TP63 gene status by FISH and for presence of Merkel cell polyomavirus by PCR. Stage emerged as a significant prognostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 25 publications
4
49
4
1
Order By: Relevance
“…In a smaller United States study (23 cases) by Bhatia et al, 22 median survival was approximately fourfold longer in polyomavirus-positive cases (86 months) than in polyomavirus-negative cases (20 months). In contrast, three subsequent studies by Handschel et al 23 (44 German cases), Schrama et al 24 (146 Australian and German cases), and Asioli et al 25 (70 Italian cases) demonstrated that 5-year overall survival is independent of Merkel cell polyomavirus status. Additionally, it does not appear that polyomavirus status influences recurrence-free survival.…”
mentioning
confidence: 89%
“…In a smaller United States study (23 cases) by Bhatia et al, 22 median survival was approximately fourfold longer in polyomavirus-positive cases (86 months) than in polyomavirus-negative cases (20 months). In contrast, three subsequent studies by Handschel et al 23 (44 German cases), Schrama et al 24 (146 Australian and German cases), and Asioli et al 25 (70 Italian cases) demonstrated that 5-year overall survival is independent of Merkel cell polyomavirus status. Additionally, it does not appear that polyomavirus status influences recurrence-free survival.…”
mentioning
confidence: 89%
“…Two studies have indicated that patients with virus-negative MCC experience decreased survival as compared with patients with virus-positive MCC [83,84]. Conversely, several others have reported no significant survival difference between the two groups [85][86][87]. Importantly, genetic analysis indicates that these two subsets are etiologically distinct [88][89][90].…”
Section: Virus-negative Mccs and Uv-induced Neoantigensmentioning
confidence: 99%
“…Factors recognized as associated with poor prognosis are size of the tumor and presence of metastases according to the AJCC staging (4,47,55,(64)(65)(66)(67)(68), and immunosuppression (65,69,70). Recently, histological and immunochemistry markers have been described as potentially associated with poor outcome like low tumor infiltrating CD8 + T cells (101) and P53 and P63 expression and gen mutations (54, 68, 74) ( Table 2).…”
Section: Mcpyv Status and MCC Prognosismentioning
confidence: 99%